The Effect of Playdough Media Play on Early Childhood Development: Fine Motor and Cognitive - Yuniyartika, Yuniyartika; Sudaryanti, Sudaryanti (STKIP Singkawang, 2024)
Efforts to improve children's fine motor skills are an indispensable effort in growing and developing early childhood, one of which is using the media of playdough games. This study aims to find out (1) whether there is an effect of playdough media on the fine motor development of group B children at Pembina Sekayu State Kindergarten, (2) whether there is an effect of playdough media on the cognitive development of group B children at Pembina Sekayu State Kindergarten. This study is a quasi-experimental research with a nonequivalent control group design, the population of this study is all children aged 5-6 years at Pembina Sekayu State Kindergarten, with a sample of 60 children. The instrument used was in the form of observation techniques for the fine motor and cognitive development of children. The data analysis technique used independent sample t-test analysis with a significance level of 0.05. The results of the study showed that: (1) there was a significant influence of playdough media on the fine motor development of group B children at Pembina Sekayu State Kindergarten where the paired sample t-test results were obtained on average of 46.77 with a Sig value of 0.000 < 0.05. (2) there was a significant influence of playdough media on the cognitive development of group B children at Pembina Sekayu State Kindergarten where the paired sample t-test results were obtained on average of 52.93 with a Sig value of 0.000 < 0.05. So based on the study, it can be concluded that there is a very significant influence on playdough media games on fine motor and cognitive development in early childhood